The translation and psychometric assessment of the SCOFF eating disorder screening questionnaire: the Persian version - Shahin Bazzazian; Giti Ozgoli; Nourossadat Kariman; Malihe Nasiri; Tahereh Mokhtaryan-Gilani; Maryam Hajiesmaello (Journal of Eating Disorders, 2022)
Plain English summary Eating Disorders (EDs) are defined by abnormal eating habits that affect a person's health. Eating disorders are common in Iranian young people. Early recognition of EDs can reduce its physical, psychiatric, psychosocial outcomes, improve the prognosis, and minimize the impact on patients and their families. However, timely recognition of EDs is difficult because of the variety of signs and presentations. The SCOFF (Sick-Control-One stone-Fat-Food) is a valuable screening questionnaire for rapid identification of people at risk for EDs. This study was conducted to translate and evaluate the psychometric properties of the SCOFF questionnaire in Iranian university students. The results of our study suggest that the 5-item Persian version of the SCOFF is a valid questionnaire in EDs screening.